THE EFFECT OF TECHNOLOGY USE IN QUR'AN HADITH TEACHING ON THE LEARNING MOTIVATION OF 8TH GRADE STUDENTS AT MTS NW TANJUNG LUAR - Muhammad Syukri (Journal of Islamic Religious Studies, 2024)
Religious education, particularly the teaching of Qur'an Hadith, plays a crucial role in shaping students' character and morals in junior high school. However, in this digital era, the challenge lies in increasing students' interest and motivation to learn. This study aims to explore the impact of technology use in Qur'an Hadith teaching on the learning motivation of 8th-grade students at MTs NW Tanjung Luar. This research used a quantitative approach with a descriptive correlational design to identify the relationship between technology use and students' learning motivation levels. The sample consists of 120 purposively selected 8th-grade students. Data were collected through a structured questionnaire measuring students' learning motivation and their perceptions of technology use in Qur'an Hadith classes. Data analysis was conducted using descriptive and correlational statistics with the aid of SPSS software. The study results reveal a significant positive correlation (r = 0.58) between the use of technology in Qur'an Hadith teaching and students' learning motivation. This indicates that as technology is more frequently used in teaching, students' motivation to learn increases. The findings also note that while technology use in Qur'an Hadith teaching is at a moderate level, its impact on learning motivation is substantial. The integration of technology in Qur'an Hadith teaching can enhance students' learning motivation, making the learning experience more interactive and relevant. The practical implication of this study highlights the importance of optimal technology application in Qur'an Hadith education to improve learning quality. Further research is needed to explore the most effective types of technology and the optimal ways to implement them.